Behind the mask: Attentional focus and coping strategies of elite level fencers - Bracco, M.; Bernier, M.; Métral, L.; Pété, E.; Bagot, P.; Fournier, J.; Doron, J.; Martinent, G. (Psychology of Sport and Exercise, 2025)
This study aimed to identify attentional foci and coping strategies of elite fencers during competitive matches, explore the co-occurrences between both, and examine their impact on performance. Twenty-two epeeists (11 males and 11 females) from a national team took part in self-confrontation interviews during two simulated tournaments. Data were analysed using inductive and deductive content analyses. Moreover, a quantitative analysis of qualitative data was conducted to examine the impact of attentional foci and coping strategies on objective performance. Three categories of attentional foci were identified: (a) cues, (b) strategies and tactics and (c) extraneous attention. To depict the coping processes of elite fencers, appraisals, coping strategies and emotions were coded. Coping strategies were mainly task-oriented, and often co-occurred with strategic foci. Analysis of the co-occurrences showed that athletes could combine information from their sensations and their environment during a point. They could also use several coping strategies within or between points. Chi-square tests revealed that focusing on environmental cues, particularly spatial-temporal characteristics, was associated with more touches won and fewer touches lost. Focusing on distance/timing of actions could be relevant cues in elite fencing. Focus on internal aspects did not impair performance in the present sample. This study furthered knowledge of attentional foci and coping strategies described by elite athletes in naturalistic settings. Following the present research results, practitioners should seek to develop pre- and post-point routines that pair task-oriented coping strategies with relevant attentional focus.